Floral development in Anemoneae, Ranunculaceae / Yi Reni; Hong-Li Chang; Peter K. Endress - Ren, Yi; Chang, Hong-Li; Endress, Peter K. (London Linnean Society of London, 2010)
The floral development of two Clematis species and four Anemone species (including Pulsatilla) (Anemoneae, Ranunculaceae) is described. Shared features are: (1) sepals shortly after initiation broad, crescent-shaped, as opposed to the other organs, which are narrow and hemispherical; (2) outermost organs of the androecium often smaller than the others and sometimes sterile; (3) carpels ascidiate, with distinctive stalk, stigma papillate, decurrent; the carpels have one median fertile ovule and a few lateral sterile ovules in all species studied; the fertile ovule appears before the carpel closes. Generic differences are: (1) In Clematis, four sepals are initiated in two pairs; sometimes one of the sepals in the second pair appears to be divided into two organs (double position) resulting in a pentamerous perianth; the first eight stamens are positioned in two alternating whorls, the outer whorl alternating with the four sepals. In Anemone, the perianth organs, if five, are initiated in spiral sequence; in the Pulsatilla group of Anemone, six sepals are initiated in two whorls; the first three organs of the androecium (staminodes) alternate with the inner sepals. (2) Further androecial organs are mostly in complex whorls (i.e. including double positions) in Clematis, but in an irregular spiral or in irregular complex whorls in Anemone. (3) Anther maturation is largely centripetal in Clematis, but centrifugal or bidirectional in Anemone. In Clematis macropetala, the outermost organs of the androecium lack anthers and the filaments expand and become petal-like. In contrast, in the Pulsatilla group of Anemone, these organs retain sterile anthers and become small, capitate organs.
Botanical Journal of the Linnean Society, 2010, 162, 77-100. With 15 figures
Keywords: Anemone; Clematis; Ranunculaceae; Flor; Filotaxis